Development of the stock exchange information system - Miladinović, R. (Yugoslav Journal of Operations Research; Vol 16 No 2 (2006): Vol. 16 No. 2, 2016)
The stock exchange represents the key institution for the development of capital market of any country. Thus the information system of every stock exchange must satisfy very strict international standards. The development of these systems is particularly difficult in countries in transition, due to intense economic and legal changes, lack of technical and financial resources, lack of experience and knowledge in the area of the capital market business, etc. Therefore the special software project management methodology for their realization must be clearly defined. In the development process of the Belgrade Stock Exchange (BSE) information system a new software project management methodology for its realization has been defined, the application of which is illustrated through a series of different development stages of the Belgrade Stock Exchange information system. In order to make all the problems more comprehensive, only the continuous trading method is described, being the most frequently used trading method in the world.